ON THE NATURAL OCCURRENCE OF LABEO ROHITA (HAM.) LABEO GONIUS (HAM.) HYBRID IN DHAURA RESERVOIR (UTTAR PRADESH) INDIA AND ITS POSSIBLE ROLE IN AQUACULTURE - JOHRI, V. K.; PRASAD, RAVINDRA; SAXENA, M. P. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
A natural interspecific fish hybrid between Labeo rohita (Ham.) and L. gonius (Ham) was encountered during fishing operations in Dhaura reservoir (District Nainital, U.P.). The hybrid exhibited faster growth than Labeogonius one of the parent species. In general appearance, it was in between L rohita and L. gonius. The studies on its morphometric characters and its potential role in aquaculture are presented in the paper.